Long-term follow-up of patients with displaced scapular fractures managed surgically and non-operatively. Issue 6 (June 2022) - Graafland, M.; van de Wall, B.J.M.; van Veelen, N.M.; van Leeuwen, R.; Hoepelman, R.J.; Knobe, M.; Link, B.C.; Babst, R.; Beeres, F.J.P.
Abstract: Introduction: Controversy remains on which patients with displaced scapula fractures benefit from surgery. This retrospective cohort study aims to compare and describe long-term patient-reported outcomes of patients with displaced scapula fractures treated both surgically and conservatively. Methods: This study included patients with intra- and extra-articular scapula fractures, treated between 2010 and 2020 in a Swiss level 1 trauma centre. The decision to operate was based on standardized criteria for fracture displacement. Patients with isolated Bankart lesions (Ideberg 1) and process fractures (AO type 14-A) were excluded. Primary outcomes were functional patient reported measures (DASH score) and quality of life (EQ5D score). Secondary outcomes were complications, radiological union, satisfaction with treatment, pain and range of motion. Results: Out of 486 cases, 74 patients had displaced scapula fractures. Forty patients were treated surgically and 34 were treated conservatively. Significantly more patients with intra-articular fractures and high-energy trauma were treated surgically. Fifty percent returned the questionnaires after a mean follow-up of 47 months (± SD 36). The mean DASH score of this group was 12 (SD 15.6), with a mean of 14.7 (SD 15.9) in the surgery group and 9.8 (SD 14.6) in the non-operative group (p = 0.7). Multivariate analysis did not show statistically significant correlating factors. No significant differences in quality of life were observed. Patients rated their treatment with a mean of 8.6/10 (SD 1.8). Among surgically treated patients, 19 underwent a deltoid sparing procedure with significant shorter time to union than those that underwent deltoid release (23 vs. 49 weeks, p<0.01). Complications occurred in 3/28 surgically treated patients and all three required a reoperation. Conclusion: In this cohort, functional results after conservative and surgical treatment were similar, despite more complex fractures and more intra-articular fractures being treated surgically. Osteosynthesis of both intra- and extra-articular scapula fractures is safe and leads to good functional results, furthermore, new minimal invasive techniques may lead to faster bone healing and return to work and sports